Contributions of education research to the public debate and the design of policies - María Catalina Nosiglia (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2016)
This paper reflects part of the work carried out in a Forum of the "30 years of educational research in Argentina" Conference, whose purpose was to share, discuss and ponder on the contributions of social and educational research to the public debate and the design of educational policies. As it has been pointed out in several studies that addressed these complex relations, although there are several formal public documents that look forward to the use and application of social and education research, the real use of these research has been scarcely inquired on an international level. This article aims to reflect, as an essay, on the relationship between the production of scientific knowledge in the field of educational policies and its use in the formulation, implementation and evaluation of educational policies. Theoretical contributions that were interesting to us have been incorporated to analyze how these elements are articulated and issues discussed at the Forum to analyze especially the argentine context.